Business Model Development with Business Model Canvas Approach and SWOT Analysis at PT. Kita Muda Bisa - Prabowo Leksono, Teguh; Riza Sutjipto, Mohammad; Witjara, Edi (Green Publisher Indonesia, 2025)
In an era characterized by rapid technological advances and continuously evolving consumer preferences, companies are required to continue to innovate and optimize their strategies to maintain relevance and competitiveness in the market. With this background, this research focuses on PT Kita Muda Bisa, a company that has an online learning platform in Indonesia, which is specifically involved in the world of pre-employment which facilitates online learning services to the community. By using a qualitative research approach, this study aims to gain in-depth insight into the current condition of the business model and strategic landscape of pre-employment training institutions in Indonesia. Through a comprehensive analysis using the BMC and SWOT frameworks, this research seeks to identify existing strengths and weaknesses, as well as external opportunities and threats related to training service products. By utilizing this analysis, this research seeks to develop an understanding of the complex interactions between internal capabilities and external market dynamics that shape the competitiveness of learning service products in Indonesia. The proposed strategy is designed to exploit strengths, mitigate weaknesses, exploit opportunities, and counter threats identified through the research process. Additionally, this research highlights the importance of strategic agility and adaptability in navigating the dynamic training industry landscape, emphasizing the need for continuous strategy reassessment and refinement. In Conclusion, this research contributes to existing knowledge by offering practical insights and recommendations to increase the competitiveness of online learning service products. By integrating the BMC and SWOT frameworks, this research provides a qualitative approach to strategic analysis and formulation, equipping PT Kita Muda Bisa's work plan with the tools and insights needed to thrive in an increasingly competitive market. Ultimately, the findings of this research aim to inform the strategic decision-making process in online learning services and inspire similar efforts in a broader business and innovation strategic context.